The solutions of x(x - 3) = 2 may be expressed in the form (a + sqrt(b))/c and (a - sqrt(b))/c, where a, b, and c are prime numbers. Find a + b + c.

Guest Dec 31, 2020

#1**0 **

Hello Guest!

To start, let's turn the equation to the form ax^2 + bx + c = 0 so we can apply the quadratic equation.

x(x - 3) = 2

x^2 - 3x = 2

x^2 - 3x - 2 = 0.

Now we just plug everything in. :))))

Here's the formula if you need it: https://en.wikipedia.org/wiki/Quadratic_equation#/media/File:Quadratic_formula.svg

x = (3 + sqrt(17))/2 or x = (3 - sqrt(17))/2

Now, we just do addition. 3 + 17 + 2 = 22.

I hope this helped. :)))

=^._.^=

catmg Jan 1, 2021